Work intensification: Towards mapping the study field and defining a research agenda - Lemos, Ana Heloísa da Costa; Campos, Waleska Yone Yamakawa Zavatti; Quintão, Marcelo Jucá; Rosa, Luciana Aparecida Barbieri da (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
Work intensification can be defined as the increase in energy expenditure by the worker in the exercise of his current occupations. Given the complexity of the phenomenon, this study aimed to analyze the scientific literature on work intensification to map the field and propose a research agenda. Three approaches were developed from 98 articles extracted from the Web of Science, namely bibliometric, scientometric, and content analyses. The findings reveal that the scientific production on the subject had a significant increase between 2010 and 2019; predominant themes are work-family conflict, repetitive strain, and teleworking, among others. Furthermore, the research agenda reveals rich possibilities for gaps and future studies.